2008
DOI: 10.1088/0266-5611/24/4/045010
|View full text |Cite
|
Sign up to set email alerts
|

Solution of the nonlinear elasticity imaging inverse problem: the compressible case

Abstract: We have recently developed and tested an efficient algorithm for solving the nonlinear inverse elasticity problem for a compressible hyperelastic material. The data for this problem are the quasi-static deformation fields within the solid measured at two distinct overall strain levels. The main ingredients of our algorithm are a gradient based quasi-Newton minimization strategy, the use of adjoint equations and a novel strategy for continuation in the material parameters. In this paper we present several exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 47 publications
(84 reference statements)
1
93
0
Order By: Relevance
“…Young's modulus (Guo et al 2010) or a general linear elasticity tensor (Raghupathy and Barocas 2010), can be determined directly from the force equilibrium equation iteratively (Moulton et al 1995;Govindjee and Mihalic 1998;Kauer et al 2002;Seshaiyer and Humphrey 2003;Bosisio et al 2007;Lei and Szeri 2007;Samani and Plewes 2007;Gokhale et al 2008;Karimi et al 2008;Li et al 2009;Balocco et al 2010;Kroon 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Young's modulus (Guo et al 2010) or a general linear elasticity tensor (Raghupathy and Barocas 2010), can be determined directly from the force equilibrium equation iteratively (Moulton et al 1995;Govindjee and Mihalic 1998;Kauer et al 2002;Seshaiyer and Humphrey 2003;Bosisio et al 2007;Lei and Szeri 2007;Samani and Plewes 2007;Gokhale et al 2008;Karimi et al 2008;Li et al 2009;Balocco et al 2010;Kroon 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The gradient was computed using the adjoint method developed by Gokhale et al (2008) for inverse elasticity imaging (see also Oberai et al (2003)). The mathematical development of the adjoint method is reviewed briefly in the "Appendix".…”
Section: The Finite Element Modelmentioning
confidence: 99%
“…The remaining term D 魏 L evaluated to, Gokhale et al (2008) showed that Eq. (20) is equivalent to the gradient vector of the objective functional.…”
Section: Appendixmentioning
confidence: 99%
“…It could be used, for example, in surgery planning [74], for simulation of surgical procedures for training and learning purposes [10,74], to study virtual reality in clinical systems [107], in tissue engineering [3,29,60], and for finite element modelling of different organs [11,36,51]. Determining the elastic properties of soft biological materials under finite deformation is of great interest in elasticity imaging, where these material properties can be used to distinguish between malignant tissue and benign tissue and even for cancer classification [35,80,85].…”
Section: Introductionmentioning
confidence: 99%